Cooperativeness and competitiveness as two distinct constructs: Validating the Cooperative and Competitive Personality Scale in a social dilemma context. (December 2013) - Lu, Su; Au, Wing‐Tung; Jiang, Feng; Xie, Xiaofei; Yam, Paton
<x xml:space="preserve">Abstract</x> The present research validated the construct and criterion validities of the Cooperative and Competitive Personality Scale (CCPS) in a social dilemma context. The results from three studies supported the notion that cooperativeness and competitiveness are two independent dimensions, challenging the traditional view that they are two ends of a single continuum. First, confirmatory factor analyses revealed that a two‐factor structure fit the data significantly better than a one‐factor structure. Moreover, cooperativeness and competitiveness were either not significantly correlated (Studies 1 and 3) or only moderately positively correlated (Study 2). Second, cooperativeness and competitiveness were differentially associated with Schwartz's Personal Values. These results further supported the idea that cooperativeness and competitiveness are two distinct constructs. Specifically, the individuals who were highly cooperative emphasized self‐transcendent values (i.e., universalism and benevolence) more, whereas the individuals who were highly competitive emphasized self‐enhancement values (i.e., power and achievement) more. Finally, the CCPS, which adheres to the trait perspective of personality, was found to be a useful supplement to more prevalent social motive measures (i.e., social value orientation) in predicting cooperative behaviors. Specifically, in Study 2, when social value orientation was controlled for, the CCPS significantly predicted cooperative behaviors in a public goods dilemma (individuals who score higher on cooperativeness scale contributed more to the public goods). In Study 3, when social value orientation was controlled for, the CCPS significantly predicted cooperative behaviors in commons dilemmas (individuals who score higher on cooperativeness scale requested fewer resources from the common resource pool). The practical implications of the CCPS in conflict resolution, as well as in recruitment and selection settings, are discussed.